Investigation of the influence of processing conditions on the thermal, rheological and mechanical behavior of polypropylene nanocomposites. Issue 5 (28th September 2012) - Mattausch, H.; Laske, S.; Đuretek, I.; Kreith, J.; Maier, G.; Holzer, C.
Abstract The use of polypropylene (PP)‐layered silicate nanocomposite has attracted great interest in the polymer industry over the last years. On one hand, PP is widely used in many fields of applications because of good performance and cost. On the other hand, the major advantage of layered silicate nanofiller in the polymer matrix is the small amount of filler (<5 wt%) needed to enhance various properties such as Young's modulus. The most commonly used layered silicates are organomodified montmorillonite (MMT). In this study, a PP/organoclay nanocomposite, filled with layered silicate Nanofil SE3010 (1 and 5 wt%), provided by Rockwood Additives, USA, was used. The polymer nanocomposites were prepared via melt intercalation in a laboratory kneader. The compatibilizer (PP grafted with maleic acid anhydride) admixture content relative to the organoclay content (1 and 5 wt%) was chosen at a ratio of 1:1 (clay:compatibilizer). The influence of different processing conditions (rotation speed and residence time) on the thermal, rheological, and mechanical properties and the interlayer distance was investigated. It was the target to determine whether a short and intensive or a long and soft process performs better. Different properties prefer different states of dispersion of MMT in the polymer matrix. POLYM. ENG. SCI., 2013. © 2012 Society of Plastics Engineers